THE USE OF AUTHENTIC MATERIALS IN ONLINE ENGLISH TEACHING: FROM THE LEARNERS’ PERSPECTIVE - Gufron Pd. Gufron; Ainul Azmin (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2022)
ABSTRACTThe main objective of this study is to explore students' views on English teaching using authentic materials. This research was conducted in an English class where the students are staffs who are lecturers in a private university in Jakarta. An inductive qualitative research method was employed by interviewing five randomly selected respondents after teaching for 15 weeks. The data from the interview were analyzed in three steps; quotation, coding, and thematic analysis using Atlas.ti. The data analysis results showed that using authentic materials was more interesting and impressive than the ones that were not authentic and not related to the students' subject matter. Using authentic material also increases students' interest in speaking more because the topics discussed are related to students' real world. Besides, this method can increase interest in reading because students are familiar with vocabularies that are related to their majors. However, this method is not suitable for applying in a classroom where students are from different majors.ABSTRAKTujuan dari penelitian ini adalah untuk mengeksplorasi pandangan siswa tentang pengajaran bahasa Inggris menggunakan bahan ajar yang otentik. Penelitian ini dilakukan di kelas Bahasa Inggris dimana mahasiswanya adalah staf pengajar di salah satu perguruan tinggi swasta di Jakarta. Metode penelitian kualitatif digunakan dengan mewawancarai lima responden yang dipilih secara acak setelah mengikuti pembelajaran selama 15 minggu. Data dari wawancara dianalisis menggunakan Atlas.ti. Hasil analisis data menunjukkan bahwa penggunaan materi autentik lebih menarik dan mengesankan dibandingkan dengan menggunakan materi ajar yang umum yang tidak berkaitan dengan real-life siswa. Menggunakan materi autentik juga meningkatkan minat siswa untuk berbicara lebih aktif di ruang kelas karena topik yang dibahas berkaitan dengan jurusannya. Selain itu, metode ini dapat meningkatkan minat baca karena siswa terbiasa dengan kosa kata yang berhubungan dengan disiplin ilmunya.